KEMAMPUAN BERPIKIR TINGKAT TINGGI MAHASISWA DALAM MEMECAHKAN MASALAH FUNGSI PEMBANGKIT - Novia Dwi Rahmawati; Gunanto Amintoko; Siti Faizah (Jurnal Pembelajaran Matematika, 2018)
Abstract: The material for generator functions in discrete mathematics courses is considered as difficult material for students. In improving ability to solve problems in generator function material, the first step that should be done is recognizing and knowing students’ thinking skill comprehensively. The ability of higher order thinking (Higher Order Thinking Skills / HOTS) in this study includes the ability of logical and reasoning, analysis, evaluation, and creation. The aim of this study is to describe students’ high level thinking ability in solving generator functions problems. This research is a descriptive study with a qualitative approach. The research subjects are 6 students of the mathematics education department at Hasyim Asy'ari University. The results show that 2 students have less ability to perform logical and reasoning abilities. They are good ability in analysis, evaluation, and creation. So, they are classified as having a high level of thinking ability with moderate level. Moreover, 4 students are not able to perform logical and reasoning abilities. However, they have good ability in analysis, evaluation, and creation. So, they are classified as having high level thinking skills with low level.Keywords: HOTS, Problem Solving, Discrete Mathematics.